Dostoevsky. - Frank, Joseph, 1918-2013 (Princeton University Press, 1983)
This present volume is the second in a series dealing with the life and works of Dostoevsky ... during the ten years [he] spent first in solitary confinement, then in a prison camp in Siberia, and finally as a soldier in one of the Siberian regiments of the Russian army. --Preface.